Effect of hypothermia for perinatal asphyxia on childhood outcomes - Jose, Santhosh; K., Mohamad Ismael (International Journal of Contemporary Pediatrics, 2017)
Background: Perinatal asphyxia, neonatal asphyxia or birth asphyxia is the medical condition resulting from deprivation of oxygen to a new born infant that lasts long enough during the birth process to cause physical harm, usually to the brain. This study was performed to evaluate study population who were 6 to 8 years of age to determine whether the application of moderate hypothermia after perinatal asphyxia is associated with long term benefits. Methods: This study was a randomised, controlled trials which consisted of infants who were admitted with moderate and severe encephalopathy within 6 hours after birth after an acute perinatal event, with acidosis or resuscitation. Infants were assigned to undergo whole body hypothermia at 33ºC for 72 hours or to undergo usual care randomly. Results: All maternal baseline characteristics and Neonatal characteristics are non significant in both groups. APGAR score ≤5 is significant at 10mins in comparison. cerebral palsy were 18% and 25%, respectively, the rates of blindness were 1% and 4% the rates of hearing impairment (requiring aids) were 5.4% and 12.8%. There were no significant between-group differences in the level of disability among all survivors or in motor function among the 45 nondisabled children. Among children who had moderate or severe disability at 18 months, the corresponding rates at 6 to 7 years of age were 88% in the hypothermia group and 95% in the control group. All the children who had moderate-to-severe cerebral palsy at 18 months continued to be affected at 6 to 7 years in both groups. There was no significant between-group difference with respect to IQ scores that were measured on a continuous scale and other scores, with the exception of 1 of the 11 scores compared (attention and executive function, P=0.03). There were also no significant differences between groups in mean scores on the index of health care status derived from parental assessments or in parental scores for children’s strengths and difficulties and ADHD The mean difference in the academic achievement score favored the hypothermia group but was not significant. Conclusions: Moderate hypothermia after perinatal asphyxia resulted in improved neurocognitive outcomes in middle childhood.